Tandem [5,5]-/[3,3]-Rearrangements of Aryl Sulfoxides with Allyl Nitriles - Hu, Mengjie; Ru, Liying; Zhu, Mengjiao; Yang, Shengwen; Fan, Suojiang; Ji, Jiangtao; Zheng, Dingming; Peng, Bo (Synthesis, 2024)
Tandem aromatic rearrangements represent a potent strategy for modulating the regioselectivity of a rearrangement process. In this article, we disclose two novel tandem aromatic rearrangements triggered by sulfonium [5,5]-rearrangement recently developed in our laboratory. Specifically, the [5,5]-rearrangement of aryl sulfoxides with allyl nitriles, followed by [3,3]-Cope rearrangement, forges a seamless tandem [5,5]-/[3,3]-rearrangement cascade, affording ortho-functionalized aryl sulfides. The other tandem process involves [5,5]-rearrangement of aryl sulfoxides with allyl nitriles, followed by nucleophilic addition/DDQ-oxidation-induced [3,3]-Cope rearrangement, eventually yielding meta-functionalized aryl sulfides. Both consecutive rearrangements enrich the repertoire of tandem aromatic rearrangement methodologies.
Keywords: aromatic Claisen rearrangement; [5,5]-rearrangement; tandem rearrangement; sulfur; nitrile